Development of an integrated manufacturing performance measurement and evaluation framework - Huang, Kuang-Chung (Cranfield University, 2000)
With the end of the Cold War and the subsequent reduction in defence spending, the Taiwanese defence industry has encountered great difficulties. Recently, the Government announced that at the end of 2006, all military plants should move from the public sector to the private sector. The aim being not only to maintain a manufacturing capability sufficient to ensure the technical competence and resources necessary for an effective and timely response to a mobilisation but also to reduce government infrastructure costs. However, unless the military plants take more aggressive action to assess their management and manufacturing weaknesses effectively, their modernisation efforts will not succeed. This research is concerned with the development of a methodology for manufacturing performance measurement and evaluation to help Taiwanese military plants develop and maintain a competitive advantage. The basic concept of the proposed framework is based on the Balanced Scorecard concept. However, the structure and procedures have been further developed to reflect Taiwan's specific requirements. In particular, the proposed framework provides a structure and tools to tackle a number of key requirements, such as the need to provide both internal and external measures as a means of both qualitatively and quantitatively prioritising and evaluating manufacturing strategic concerns, and the need to show continuously where improvement needs to be made. Industrial case studies have shown that the proposed framework is both feasible and effective when applied within the particular environment of Taiwanese military plants. In addition the proposed framework has highlighted some theoretical and practical problems associated with the design and development of manufacturing performance measurement and evaluation framework. Due to its generic nature, through interviews with three UK companies, it was demonstrated that the proposed framework could also be applied to other societies and industries, either public or private, to solve their manufacturing performance measurement and evaluation problems.